Heat pipe with nano enhanced-PCM for electronic cooling application - Krishna, Jogi; Kishore, P.S.; Solomon, A. Brusly (Experimental thermal and fluid science, 2017)
•Thermal conductivity of nano enhanced-PCM is enhanced compared to pure Tricosane.•Thermal performance of heat pipe using nano enhanced-PCM is presented.•Temperature variations of evaporator with nano enhanced-PCM are reported.•Maximum of 30% of the input power is stored in the nano enhanced-PCM.•PCM with 1vol% Al2O3 nanoparticle is found to be optimum for maximum heat transfer. In this study, the thermal performance of a heat pipe, using nano enhanced Phase Change Material (PCM) as an energy storage medium for electronic cooling applications is studied. The PCM is placed around the adiabatic section of the heat pipe in which heat is absorbed and released depending on the power inputs at the evaporator and fan speeds at the condenser. Experiments are performed to obtain the evaporator, condenser and PCM temperature distributions during the charge, discharge and simultaneous charge/discharge processes. In the present study, Water, Tricosane and nano enhanced Tricosane are used as energy storage materials. The nano enhanced PCMs are prepared by mixing different volume percentages (0.5%, 1% and 2%) of Al2O3 nanoparticles with Tricosane. The thermal conductivity of the nano enhanced PCM is measured and found to be enhanced to a maximum of 32% compared to the pure Tricosane. The effects of PCM filling volumes, fan speeds and heating power on the performance of cooling module are also investigated. From this study it is found that the evaporator temperature of the heat pipe with nano enhanced PCM is decreased about 25.75%, which can save 53% of the fan power compared to a traditional heat pipe. It was also found that the nano enhanced PCM can store almost 30% of the energy supplied at the evaporator leading to the reduction in fan power consumption.